Hubungan Persepsi Waria Terhadap Layanan Skrining HIV- AIDS di Laboratorium Puskesmas dan Penggunaan Layanannya - Ashfa Diniyya Assabela (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
HIV screening services are the main entry point for services aimed at prevention, treatment, support and treatment. The use of HIV screening services by key populations, including transgender women, is important so that HIV status is monitored. Many transgender women work as commercial sex workers, so the spread of HIV is a cause for concern, so the use of HIV screening is important. The causes of the underutilization of HIV screening services need to be investigated. This study aims to examine the relationship between transgender perceptions of HIV screening services in the health center laboratory. The method used in this research is cross sectional with interview method. 80 transgender women in PERWAKOS were interviewed fulfilling the inclusion and exclusion criteria. The data were analyzed using the bivariate test to determine the relationship, the multivariate test to determine the simultaneous relationship, and the binary multiple regressions test on the IBM SPSS Statistics 23.0 for Mac software. Result: The sample size was 80 and it became 73. As many as (78%) 57 chose no stigma, (79.5%) 58 chose fast waiting time, (84.9%) 62 chose the distance from home to a close laboratory, (60.3 %) 44 perceived complete, (53.4%) 39 chose less professional. There is a relationship between the perception of transgender women on stigma by the laboratory staff (p = 0.000), the distance from the house to the laboratory (p = 0.000) and HIV screening services in the health center laboratory. In conclusion, there is a relationship between transgender perceptions of stigma by laboratory assistants, the distance from the house to the laboratory and the use of its services.